Traffic Management and Engineering on Erlangga Timur Street, Semarang City, Central Java - Farhan Sholahudin; Syamsul Ma'arif; Muhammad Ramadhan (Fakultas Teknik, Universitas Wiraraja, 2026)
In the role of transportation, there are two main elements that need to be considered: road volume and capacity. When the number of vehicles continues to increase without a corresponding improvement in road capacity, traffic problems such as congestion, accidents, and decreased efficiency of road segments become inevitable. This study aims to evaluate traffic management and engineering on Jalan Erlangga Timur, with a focus on identifying problems and developing effective and sustainable solutions. The methodology includes traffic volume surveys, road infrastructure inventory, vehicle speed measurements, and analysis of the road’s Level of Service. The analysis was carried out based on the Indonesian Road Capacity Guidelines (PKJI) 2023. In addition, this research also considers traffic condition forecasting for the next two years to maintain or improve the performance of the road segment. Findings indicate that Jalan Erlangga Timur experiences significant congestion during peak hours, with a Level of Service categorized as F, indicating highly unstable and disrupted operational conditions. The proposed recommendations include increasing road capacity, priority management, and demand management to improve road performance. The primary contribution of this research lies in providing a technical database and strategic recommendations for the Semarang City Government to optimize traffic management. This study goes beyond documenting existing conditions by offering sustainable solutions to transform underperforming road segments into more efficient and safer transportation corridors